PITX2 expression and Neanderthal introgression in HS3ST3A1 contribute to variation in tooth dimensions in modern humans - Liu, Qing (2024)
Dental morphology varies greatly throughout evolution, including in the human lineage, but little is known about the biology of this variation. Here, we use multiomics analyses to examine the genetics of variation in tooth crown dimensions. In a human cohort with mixed continental ancestry, we detected genome-wide significant associations at 18 genome regions. One region includes EDAR, a gene known to impact dental features in East Asians. Furthermore, we find that EDAR variants increase the mesiodistal diameter of all teeth, following an anterior-posterior gradient of decreasing strength. Among the 17 novel-associated regions, we replicate 7/13 in an independent human cohort and find that 4/12 orthologous regions affect molar size in mice. Two association signals point to compelling candidate genes. One is ∼61 kb from PITX2, a major determinant of tooth development. Another overlaps HS3ST3A1, a paralogous neighbor of HS3ST3B1, a tooth enamel knot factor. We document the expression of Pitx2 and Hs3st3a1 in enamel knot and dental epithelial cells of developing mouse incisors. Furthermore, associated SNPs in PITX2 and HS3ST3A1 overlap enhancers active in these cells, suggesting a role for these SNPs in gene regulation during dental development. In addition, we document that Pitx2 and Hs3st3a1/Hs3st3b1 knockout mice show alterations in dental morphology. Finally, we find that associated SNPs in HS3ST3A1 are in a DNA tract introgressed from Neanderthals, consistent with an involvement of HS3ST3A1 in tooth size variation during human evolution.